Coleta seletiva e percepção ambiental em alunos do ensino fundamental no município de Monteiro Lobato - SP - Silva, Gerusa Corrá da (2014)
This paper discusses the knowledge of elementary school students II, the city of Monteiro Lobato - SP, on waste issues. The city faced problems in selective collection, which is no longer held for several months and was redeployed in early 2014. The technique used for data collection was the application of questionnaires and then analyze the data in an attempt to evaluate the behavior students on the issues relating to waste disposal, waste sorting, recycling and reuse in order to analyze the knowledge and habits of students in homes and at school. In addition we tried to infer participation in selective collection, and the students' knowledge about the problems caused by improper disposal of waste, as well as the municipality's responsibility for recycling and how recycling is done in an attempt to raise awareness and value recycling and reuse practices for the conservation of the environment. The school comes as an ally and should be emphasized as an element for the transformation of the community. Through environmental awareness can be established awareness tools in search of an awareness, change attitudes aimed at improving environmental quality, as well as preservation and conservation. As discussed in the present work is needed greater incentives in environmental education in an attempt to educate students and the public, because it was concluded that the selective collection, recycling and reuse of materials are still issues that must be addressed much among students. Most do not realize these practices to improve the disposal of waste. Increased awareness and understanding of the importance of actions to promote awareness of students and the community in the separation and proper disposal of garbage is required in an attempt to avoid possible problems to the environment and contribute to an improvement of the environment in which we live.